A complex treatment with orthodontic modification of the alveolar axis for implant insertion in a patient over 65 years of age with a thin periodontal biotype - Dragos Epistatu; Andreea Baco; Florin Dogioiu; Valentin Varlas; Iulian Damian; Ioanina Parlatescu; Elena Terecoasa; Mihai Sandulescu; Ion Popovici; Paula Perlea (Amaltea Medical Publishing House, 2021)
The case of a 69-years-old patient with flared anterior teeth (bi-pro-alveolar position with loose of contact points) secondary to periodontitis, was resolved by combining alveolar maxillary preservation with orthodontic treatment to correct the alveolar axes of the mandibular incisors. All mandibular teeth were finally removed but the implants could be placed in the correct antero-posterior tilt axes. The temporary maxillary prosthesis was a removable one under conditions of a thin gingival biotype. The final result meant the correction of the profile and a good preservation of the minimally keratinized gingiva around implants.